The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/jcm8040421
|View full text |Cite
|
Sign up to set email alerts
|

Phasic Left Atrial Function in Cancer Patients Before Initiation of Anti-Cancer Therapy

Abstract: : We aimed to explore left atrial (LA) remodeling in the patients with solid cancer before initiation of chemo- or radiotherapy. This retrospective investigation included 92 chemo- and radiotherapy-naive cancer patients and 40 age- and gender-matched controls with a similar cardiovascular risk profile as the cancer group. All participants underwent comprehensive echocardiographic examination before the start of chemo- or radiotherapy. LA phasic function was evaluated in volumetric and strain method. Indexed mi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 26 publications
4
9
0
2
Order By: Relevance
“…Recent published data has proved similar associations between LV systolic dysfunction and LA enlargement and impairment [10,28,40]. Moreover, in our diseased group, LVEF's deterioration was closely related with LA dysfunction, similar to other reports [41].…”
Section: Discussionsupporting
confidence: 91%
“…Recent published data has proved similar associations between LV systolic dysfunction and LA enlargement and impairment [10,28,40]. Moreover, in our diseased group, LVEF's deterioration was closely related with LA dysfunction, similar to other reports [41].…”
Section: Discussionsupporting
confidence: 91%
“…In our study, mean value of RVEDV increaseis not statistically signicant (p=0.057), however the number of patients who shows increased in RVEDV was 12.72% (7 of 55) of the patients. Inpost RT phase the mean value increased to 137.26 SD ± 4.28 which was signicant (p=0.008) similar to other studies 16. Marijana Tadic et al reported greater diameter and higher volume among patients undergoing chemotherapy and radiation.…”
supporting
confidence: 84%
“…LA conduit function was found to be defective even before LV hypertrophy and enlargement occurred [ 34 ], and to be directly associated with diastolic dysfunction, its severity [ 32 ] and progression [ 35 ]. Moreover, LA reservoir function was notably linked to cardiac dysfunction in diabetic [ 36 ] and cancer patients [ 37 ]. Additionally, the role of LA strain had been certified, being considerably linked to disease severity, HF hospitalization and mortality [ 38 ].…”
Section: Discussionmentioning
confidence: 99%